Influence of Nitrogen on Corrosion Resistance of Thin Ti–O–N Films Deposited by Reactive Magnetron Sputtering; Inorganic Materials: Applied Research; Vol. 12, iss. 4 - Boytsova E. L. Elena Lvovna (2021, 2021)
Title screen